2017
DOI: 10.3892/etm.2017.4205
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory response associated with choke vessel remodeling in the extended perforator flap model

Abstract: Ischemic necrosis of the surgical flap is a common complication. The behavior of choke vessels has an important role in skin flap survival. However, the mechanism of choke vessel remodeling has remained elusive. The purpose of the present study was to investigate the possible association between inflammatory responses and choke vessel remodeling in the extended perforator flap model in rats. After flap elevation, the animals were randomly divided into three groups (n=6 in each) for tissue analysis at three, fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Qing et al . reported increased levels of MCP-1 in the flap areas where growth of choke vessels was detected, thereby leading to increased vascularisation of the distal part of the flap [ 5 ]. In their study, peak values of MCP-1 were recorded on POD 5 with decreasing MCP-1 concentrations on POD 7, indicating a decline in MCP-1 expression once new vessels have formed, which might again be in line with our findings at POD 7.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Qing et al . reported increased levels of MCP-1 in the flap areas where growth of choke vessels was detected, thereby leading to increased vascularisation of the distal part of the flap [ 5 ]. In their study, peak values of MCP-1 were recorded on POD 5 with decreasing MCP-1 concentrations on POD 7, indicating a decline in MCP-1 expression once new vessels have formed, which might again be in line with our findings at POD 7.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence suggesting that the sprouting of microvessels from a pre-existing network is triggered by an inflammatory environment [ 4 ]. Even though some of the principles involved in flap survival have been elucidated, distal flap necrosis remains one of the most feared complications in the clinical setting [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the multiterritory perforator flap model was performed according to our previous study 21. Briefly, the rats were anesthetized with pentobarbital sodium anesthesia (30 mg/kg, intraperitoneal).…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have revealed that necrosis usually occurs away from the boundary between potential and dynamic territory ( Taylor et al., 1992 ; Fichter et al., 2016 ). Occurrence of necrosis increases the number of surgeries and is directly lead to a patient's dissatisfaction with the treatment ( Gill et al., 2004 ; Qing et al., 2017 ). Choke vessel as a kind of resistant vessel that connected two contiguous angiosomes ( Taylor and Palmer, 1987 ).…”
Section: Introductionmentioning
confidence: 99%